Questioning Blacks` existence in America: Toni Morrison`s vision of black beauty in "God help the child" - Ettien, Yapo (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The objective of this paper is to examine the issues of African American identity by questioning Blacks` existence in America. Indeed, in "God Help the Child" Toni Morrison renders black beauty a central issue. In seeking to sublimate black beauty in general, and particularly that of the African American woman, the writer makes a relatively humiliating presentation of the African American woman through Bride, the protagonist, who appears to be an abject character under the stigmatization of the black race.
Keywords: Blacks` existence; identity; stigmatization; constructivist shifting; femininity; colorism